Website Prototype As a Digital Based Media Promotion at PT Fei Fan International: Perancangan Prototype Website Sebagai Media Promosi Berbasis Digital Pada PT Fei Fan International - Hidayat, Amanda Fauziyah; Prajana, Adya Mulya; Razi, Aria Ar (Program Studi Desain Komunikasi Visual. Fakultas Arsitektur dan Desain Jalan Raya Rungkut Madya, Gn.Anyar, Surabaya, Jawa Timur 60294, 2023)
Tourism has become a major sector of world’s economic development including Indonesia. The contributions of tourism in Indonesia have increased annually. Pandemic sped up the digital transformation economy in Indonesia, where people have been using technology for daily basis. Business owners have made a lot of innovations in response to the changing. PT Fei Fan International is one of a company in the tourism sector that needs an innovation to respond to the changing in the industry. However, they still have no media that can support companies in responding to the changes. The process of data collection using interviews, observation, also distributed questionnaires and reviewed websites’s related literature. Then analyzed the data using SWOT analysis, and visual analysis comparison matrix. The output is to design the company prototype website and media promotions that will help PT Fei Fan International to respond to the interaction changes from conventional to digital.